Teroris Ke-Agama’an, Bukan Agama - Neri Widya Ramailis; Abdul Munir (SISI LAIN REALITA, 2017)
Religious Terrorism is different from religion it self. It is an act of terrorism that uses religion as a mask and a horse to reach its destination. The use of Religion legitimizes acts of terrorism by the offender group due to the silting of the understanding of the scriptures. This condition does not only give a bad image to religion, especially Islam, it also has implications of discrimination against Muslims primarily when associated with international policies concerning counter terrorism.